Branding Wisata Tanjung Gading Melalui Merchandise - Winarni, Winarni; Chandra, Diva Oryza Afrial; Gitayana, Nur Fitri; Wahyuningtyas, Aa Maylia; Dari, Nurma Yulan; Abidah, Nakhwah Fadiyatul; Musa, Abdullah; Rerung, Federika; Thahira, Safrina Yasifa; Pratama, Hardi Wira; Ar Ridwan, Muhammad Haikal (Abdimas Universal, 2026)
Tanjung Gading Tourism is located in Karang Joang Km 12, North Balikpapan, East Kalimantan. This tourist attraction offers the appeal of beautiful, cool natural surroundings and is equipped with facilities such as boat tours, camping, interesting photo spots, a playground, gazebos, and local cuisine. Despite its great potential for development, this destination does not yet have merchandise that represents Tanjung Gading Tourism as souvenirs for visitors. Merchandise can be an alternative medium for branding and promoting tourism. The solutions provided through this community service program are (1) creating various merchandise designs, including mugs, tumblers, key chains, aromatherapy candles, T-shirts, and tote bags with identities that represent Tanjung Gading Tourism; (2) providing merchandise production training; and (3) basic digital marketing training. In addition, intensive assistance was provided for production, promotion, and sales. The questionnaire results showed that during the program, the partners/participants, consisting of around 23-36 members of Pokdarwis and the managers of Tanjung Gading Tourism, were very enthusiastic, with more than 90% participating, the participants' skills improving by 100%, and the questionnaire results also showed a positive response rate of 99%. After receiving training and guidance, the participants/partners were also very satisfied and felt greatly assisted by this program. The partners have also successfully produced Tanjung Gading Tourism merchandise and marketed it to visitors. This not only has a positive impact on the branding and promotion of Tanjung Gading Tourism but also increases economic potential and income opportunities for the local community, particularly the Pokdarwis of Tanjung Gading Tourism.